2021
DOI: 10.1186/s13071-021-05024-6
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegypti: egg morphology and embryonic development

Abstract: Background The diseases for which Aedes aegypti is a vector are worrisome. The high vector competence of this mosquito, as well as its anthropophilia and ability to adapt to the urban environment, allows it to exploit many habitats, making its prevention an arduous task. Despite current disease control measures focused on the mosquito, the effectiveness in containing its dispersion still requires improvement; thus greater knowledge about this insect is fundamental. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
1
8
2
Order By: Relevance
“…On egg morphology, its SEM images in Figs. 1 and 2 show damages to the exochorionic meshwork and tubercles of the outer cells on exochorion cuticle (external chitin layer) with cell borders, papillae, and aeropyles 40,41 . Moreover, the cell borders and papillae as well as aeropyles were covered with a layer that was assumed to be an oil layer, which would explain the ovicidal mechanism of the EO, discussed in the paragraph below.…”
Section: Discussionmentioning
confidence: 99%
“…On egg morphology, its SEM images in Figs. 1 and 2 show damages to the exochorionic meshwork and tubercles of the outer cells on exochorion cuticle (external chitin layer) with cell borders, papillae, and aeropyles 40,41 . Moreover, the cell borders and papillae as well as aeropyles were covered with a layer that was assumed to be an oil layer, which would explain the ovicidal mechanism of the EO, discussed in the paragraph below.…”
Section: Discussionmentioning
confidence: 99%
“…and Bova et al . [ 25 , 28 ]. The differences observed were ascribed to variations in geographical origin, topographical features of the study sites, diverse climatic conditions, and other contributing factors.…”
Section: Discussionmentioning
confidence: 99%
“…This study also revealed that the eggs from the laboratory and field strains for all groups highlighted narrower dimensions, which contradicted studies by Suman et al ., Mundim-Pombo et al ., and Win et al . [ 24 , 25 , 29 ]. In contrast, the egg index values in this study closely resembled the findings of Mundim-Pombo et al .’s study [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a holometabolous insect, the biological cycle of A. albopictus involves egg, larval, pupal, and adult stages. Embryogenesis of the mosquito is a complex process involving rapid cell proliferation and organogenesis [ 46 ]. Therefore, it makes sense that a relatively high proportion of differentially expressed genes (DEGs) and more complex ceRNA networks were identified in the E vs. L1 comparison group.…”
Section: Discussionmentioning
confidence: 99%